Integrated Education: Integration of Islamic Values, Nationality, and Diversity in Learning - Siraj; Sayni Sarah; Muhammad Chairil Abnu; Atta Illah; Bengi Sara Simehate (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Teachers has not optimally applied Islamic values, nationality and nationality in learning. This is due to incomprehension and it is difficult for teachers to integrate these values in learning. The purpose of the study is to describe the implementation of Islamic values, nationality, and local wisdom that will be integrated in the learning process. The type of research used is descriptive qualitative. Data collection using in-depth interviews, participant observations; and documentation studies. Data analysis techniques are data reduction, data presentation, and conclusion drawing. Integrated education aims to develop the ability and disposition as well as civilization with dignity, quality, character and competitiveness spirit and aims to become a human being who is knowledgeable and devout, creative, independent and responsible and devoted to Allah swt. The integration of Islamic values, nationality and nationality in learning boils down to building the character of students through habituation patterns and the creation of a conducive school environment, attitudes and behaviors, so that students have academic, skilled and noble character abilities that are useful for the religion of the nation and state.